Low-temperature-resistant anti-crack epoxy asphalt concrete for seepage-proofing panel around pumping and storage reservoir and preparation method thereof
Through the multi-stage synergistic modification process of modified composite fibers, the low-temperature crack resistance of epoxy asphalt concrete used for the anti-seepage panels around the reservoir of pumped storage power stations has been improved, solving the problem of brittle cracking in the existing technology and making it suitable for complex hydraulic environments.
Patent Information
- Application Number
- CN202510752616.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-06
- Publication Date
- 2025-09-26
- Estimated Expiration
- 2045-06-06
AI Technical Summary
The asphalt concrete used in the anti-seepage panels around the reservoirs of existing pumped storage power stations is prone to brittle cracking in low-temperature environments, causing microcracks to expand and form through-cracks, affecting the structural integrity and anti-seepage performance.
Modified composite fibers are used to prepare low-temperature resistant and crack-resistant epoxy asphalt concrete through a multi-stage synergistic modification process, including the synergistic effect of basalt fiber, polypropylene fiber, graphene oxide and molybdenum disulfide to improve the low-temperature crack resistance of the material.
It significantly improves the low-temperature crack resistance and fatigue resistance of epoxy asphalt concrete, is suitable for complex hydraulic environments, and extends the service life of anti-seepage panels.
Smart Images

Figure BDA0005437823220000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of asphalt preparation, in particular to low-temperature resistant and crack-resistant epoxy asphalt concrete for anti-seepage panels around pumped storage reservoirs and a preparation method thereof. Background Art
[0002] During operation, the anti-seepage panels surrounding pumped-storage power stations are exposed to the elements for extended periods of time. When faced with sudden drops in winter temperatures, shrinkage stresses develop within the asphalt concrete. Currently used asphalt concrete generally lacks flexibility, which can easily lead to microcracks that gradually expand and eventually form through-hole cracks. These cracks not only undermine the integrity of the reservoir panel structure but also accelerate hydraulic erosion and freeze-thaw cycle damage, seriously impacting the reservoir's anti-seepage performance and service life.
[0003] The existing technology uses external additives such as fiber reinforcement materials to modify asphalt concrete to enhance the toughness of asphalt concrete. The fiber reinforcement materials mainly used include mineral fibers and plant fibers. The fiber reinforcement materials used in the existing technology still have the following problems:
[0004] 1. Although plant fibers have advantages such as low cost and wide availability, their mechanical strength is insufficient to meet the engineering mechanics requirements of anti-seepage panels around pumped storage power stations.
[0005] 2. Mineral fibers have good mechanical properties, but the crack resistance of ordinary mineral fibers at low temperatures is not fully demonstrated and cannot be well applied in complex hydraulic environments. Summary of the Invention
[0006] The present invention addresses the shortcomings of existing technologies by providing a low-temperature, crack-resistant epoxy asphalt concrete for anti-seepage panels around pumped storage reservoirs and a preparation method thereof. The concrete comprises fine aggregate, coarse aggregate, mineral powder, matrix asphalt, rubber powder, epoxy resin, a curing agent, and modified composite fibers, which are prepared through a multi-stage synergistic modification process. This invention significantly improves the low-temperature crack resistance of epoxy asphalt concrete, resolving the brittle cracking problem of conventional asphalt concrete materials used in anti-seepage panels around pumped storage reservoirs under low-temperature and hydraulic conditions.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0008] A low-temperature resistant and crack-resistant epoxy asphalt concrete for anti-seepage panels around pumped storage reservoirs. The low-temperature resistant and crack-resistant epoxy asphalt concrete comprises, in parts by weight, 300-350 parts by weight of fine aggregate, 520-650 parts by weight of coarse aggregate, 100-150 parts by weight of mineral powder, 45-55 parts by weight of base asphalt, 5-7 parts by weight of rubber powder, 6-10 parts by weight of epoxy resin, 4.5-6.5 parts by weight of curing agent, and 1.5-3 parts by weight of modified composite fiber.
[0009] The preparation process of a low-temperature resistant and crack-resistant epoxy asphalt concrete is as follows:
[0010] Mix the base asphalt and rubber powder and preheat them to 165°C until the asphalt is completely melted, maintaining the temperature at around 150°C. Add the mixture of epoxy resin and curing agent into the mixing pot, then bake and preheat the coarse aggregate, fine aggregate and mineral powder to 160°C and add them to the preheated base asphalt. Control the stirring rate to around 60rpm. When the temperature reaches around 160°C, add the modified composite fiber and mix and stir. After discharging, the low-temperature resistant and crack-resistant epoxy asphalt concrete for the anti-seepage panel around the pumping reservoir is obtained.
[0011] A method for preparing a modified composite fiber is prepared by the following steps:
[0012] Step 1: Epoxycyclohexyl methacrylate (EMCA), 2-methyltetrahydrofuran (2-MeTHF), and 1,8-diazabicycloundec-7-ene (DBU) are mixed evenly, and nitrogen is introduced to protect the reagent. The temperature is raised to 50-60°C, and a magnetic stirring device is used at a speed of 90-100 rpm. A silane coupling agent KH560 is added and stirred for a sufficient reaction of 3-4 hours to obtain an intermediate for later use.
[0013] The ratio of EMCA, 2-MeTHF and DBU is 0.2 mol: 0.5 mol-0.6 mol: 0.05-0.1 mol: 45-55 Ml, and EMCA and DBU catalyze the epoxy ring-opening reaction.
[0014] Step 2: The intermediate, 1-mercaptoethyl-3-methylimidazolium bromide, and anhydrous acetone were mixed evenly, nitrogen was introduced, the temperature was maintained at 60°C-65°C, a magnetic stirring device was used, the speed was set to 70-90 rpm, and the mixture was stirred for 30 minutes. Then, a boron trifluoride ether solution was slowly added dropwise, the reaction was carried out for 2 hours, and then the acetone was removed by low-temperature distillation to obtain a modified silane coupling agent.
[0015] The ratio of the intermediate, 1-mercaptoethyl-3-methylimidazolium bromide, anhydrous acetone and boron trifluoride ether solution is 0.1 mol: 0.1-0.12 mol: 100-125 mL: 0.05-0.1 mol, and the mercapto group is introduced to react with the epoxy group.
[0016] Step 3: Dry the basalt fiber at a constant temperature of 200°C, remove it and allow it to cool naturally, then soak it in anhydrous ethanol for a long time to remove oil and impurities from its surface. Rinse it with deionized water and dry it in an oven at 70°C. Soak the basalt fiber in a 5% thioglycolic acid solution for 0.5-1 hour, remove it, rinse it with deionized water, and dry it in an oven at 70°C to obtain a basalt fiber intermediate.
[0017] The ratio of the amount of thioglycolic acid solution to the amount of basalt fiber is 800ml:80g-120g. After etching with the thioglycolic acid solution, the occurrence sites of the fiber are increased.
[0018] Step 4: Add dibenzoyl peroxide powder to an acetone solution to prepare a dibenzoyl peroxide solution with a concentration of 20%. The solution is then placed in a heatable magnetic stirring device and the temperature is controlled at 70° C. to fully dissolve the dibenzoyl peroxide. Polypropylene fiber is placed in the prepared dibenzoyl peroxide solution and placed in a thermostat at 65° C. to fully soak for 0.5-1 hour. The soaked polypropylene fiber is removed and placed in a ventilated place to dry naturally. It is then rinsed with deionized water and then fully dried in an oven set at 75° C. to obtain a polypropylene fiber intermediate.
[0019] The ratio of dibenzoyl peroxide solution to polypropylene fiber is 1L:150g-300g, and the contact angle of polypropylene fiber is reduced and the surface energy is increased.
[0020] Step 5: Add the modified silane coupling agent and ethanol solution and mix them evenly, add dilute hydrochloric acid to adjust the pH value to 4-5, maintain the temperature at 45-55°C, mix thoroughly for 1-1.5 hours, add the basalt fiber intermediate and the polypropylene fiber intermediate, stir thoroughly, take out and dry to obtain a modified fiber intermediate.
[0021] The ratio of the modified silane coupling agent, the basalt fiber intermediate, and the polypropylene fiber intermediate is 60g: 80g-120g: 150g-300g, which improves the interfacial bonding strength of the fibers.
[0022] Step 6: Disperse the graphene oxide and molybdenum disulfide powders with a 3% polyacrylate sodium (PAAS) solution and ultrasonicate at 500W. During the ultrasonication process, add a 5% FeCl3 solution dropwise using a microsyringe for 30-60 minutes to obtain a mixed solution. The modified fiber intermediate is completely immersed in the mixed solution and ultrasonicated in a water bath at 50-150W for 10-30 minutes, utilizing the cavitation effect to promote directional adsorption and uniform distribution of the nanomaterials on the fiber surface. Drying is then performed to obtain the modified composite fiber.
[0023] Among them, the usage ratio of graphene oxide, molybdenum disulfide powder, sodium polyacrylate solution, FeCl3 solution, basalt fiber intermediate, and polypropylene fiber is 2.1g-4.2g: 2.1g-8.4g: 100mL: 50mL: 80g-120g: 150g-300g. The two-dimensional lamellar structure of graphene oxide significantly improves the tensile strength and modulus of the fiber through physical interlacing and chemical bonding. At the same time, the layered structure of molybdenum disulfide can disperse stress, prevent crack expansion, and improve the fatigue resistance and toughness of the fiber.
[0024] Low-temperature-resistant and crack-resistant epoxy asphalt concrete can be used in anti-seepage panels around pumped-storage power stations.
[0025] The present invention has the following beneficial effects:
[0026] 1. The present invention prepares a low-temperature resistant and crack-resistant epoxy asphalt concrete by adding modified composite fibers. The graphene oxide in the modified composite fibers forms a three-dimensional heat-conducting network in the asphalt to inhibit low-temperature brittle cracking, and molybdenum disulfide absorbs shrinkage strain through interlayer slip. The polar groups of polypropylene fibers enhance the bonding with epoxy resin, and the thiol modification of basalt fibers improves asphalt compatibility. 3+ Cross-linking stabilizes the material distribution. This multi-scale synergistic effect enables the material to maintain excellent interfacial strength, stress dispersion, and crack resistance at low temperatures, effectively resolving the low-temperature shrinkage stress and brittle fracture issues of epoxy asphalt concrete. Furthermore, the low-temperature elasticity of the rubber powder effectively inhibits the development of thermal shrinkage cracks in epoxy asphalt concrete.
[0027] 2. The modified composite fiber preparation method of the present invention is a multi-stage collaborative modification process. An active siloxane intermediate is constructed by the epoxy ring-opening reaction of EMCA and KH560 to increase the reaction sites. Then, 1-mercaptoethyl-3-methylimidazolium bromide is introduced. Through the mercapto-epoxy addition reaction, the ionic liquid structure is introduced into the molecular chain to enhance the stability of the structure. The surface activity of basalt fiber is enhanced by mercapto etching and polypropylene fiber peroxidation treatment, respectively, to form a stable covalent bond interface with the modified silane coupling agent. The two-dimensional layered structure of graphene oxide significantly improves the tensile strength and modulus of the fiber through physical interpenetration and chemical bonding. At the same time, the layered structure of molybdenum disulfide can disperse stress, prevent crack propagation, and synergistically improve the fatigue resistance and toughness of the fiber material in low-temperature environments.
[0028] 3. The modification process of the present invention, from molecular bonding to macroscopic network construction, realizes the optimized design of the fiber-asphalt interface, so that the composite material can still maintain good performance in harsh low-temperature environments. It is particularly suitable for complex hydraulic environments and is suitable for use as anti-seepage panels around pumped storage power stations. DETAILED DESCRIPTION
[0029] The present invention is further illustrated below by way of examples, but the scope of protection of the claims of the present invention is not limited by the examples.
[0030] Example 1
[0031] (1) Preparation of modified composite fibers
[0032] Step 1: Epoxycyclohexyl methacrylate (EMCA), 2-methyltetrahydrofuran (2-MeTHF), and 1,8-diazabicycloundec-7-ene (DBU) are mixed evenly, and nitrogen is introduced to protect the reagent. The temperature is raised to 50-60°C. A magnetic stirring device is used at a speed of 90 rpm. Silane coupling agent KH560 is added and stirred for 3 hours to obtain an intermediate for use. The ratio of EMCA, 2-MeTHF, and DBU is 0.2 mol: 0.5 mol: 0.05 mol: 45 mL.
[0033] Step 2: Mix the intermediate, 1-mercaptoethyl-3-methylimidazolium bromide, and anhydrous acetone, purge with nitrogen, maintain the temperature at 60°C, use a magnetic stirrer at 70 rpm, and stir thoroughly for 30 minutes. Then, slowly add boron trifluoride etherate dropwise, react for 2 hours, and then remove the acetone by low-temperature distillation to obtain a modified silane coupling agent. The ratio of the intermediate, 1-mercaptoethyl-3-methylimidazolium bromide, anhydrous acetone, and boron trifluoride etherate is 0.1 mol: 0.1 mol: 100 mL: 0.05 mol.
[0034] Step 3: Dry the basalt fiber at a constant temperature of 200°C, remove it, and allow it to cool naturally. Then, soak it in anhydrous ethanol to remove surface oil and impurities. After removal, rinse it with deionized water and dry it in an oven set at 70°C. Soak the basalt fiber in a 5% thioglycolic acid solution for 0.5 hours. After removal, rinse it with deionized water and dry it in an oven set at 70°C to obtain a basalt fiber intermediate. The ratio of thioglycolic acid solution to basalt fiber is 800ml:80g.
[0035] Step 4: Dibenzoyl peroxide powder is placed in an acetone solution to prepare a dibenzoyl peroxide solution with a mass percentage concentration of 20%. The solution is then placed in a heatable magnetic stirring device and the temperature is controlled at 70°C to fully dissolve the dibenzoyl peroxide. Polypropylene fiber is placed in the prepared dibenzoyl peroxide solution and placed in a constant temperature device at 65°C for full soaking for 0.5 hours. The soaked polypropylene fiber is removed and placed in a ventilated place to dry naturally. It is then rinsed with deionized water and dried in an oven set at 75°C to obtain a polypropylene fiber intermediate. The ratio of dibenzoyl peroxide solution to polypropylene fiber is 1L:150g.
[0036] Step 5: Mix the modified silane coupling agent and ethanol solution, adjust the pH to 4 with dilute hydrochloric acid, maintain the temperature at 45°C, and thoroughly mix for 1 hour. Then, add the basalt fiber intermediate and the polypropylene fiber intermediate, stir thoroughly, remove, and dry to obtain the modified fiber intermediate. The ratio of the modified silane coupling agent, basalt fiber intermediate, and polypropylene fiber intermediate is 60g:80g:150g.
[0037] Step 6: Take graphene oxide and molybdenum disulfide powder, use 3% sodium polyacrylate (PAAS) solution to disperse the powder, and use ultrasonic treatment power of 500W. During the ultrasonic treatment process, use a microsyringe to dropwise add 5% FeCl3 solution, and treat for 0.5h to obtain a mixed solution. The modified fiber intermediate is completely immersed in the mixed solution, and simultaneously uses water bath ultrasonic treatment with power of 50W for 10 minutes. After drying, a modified composite fiber is obtained. The ratio of graphene oxide, molybdenum disulfide powder, sodium polyacrylate solution, FeCl3 solution, basalt fiber intermediate, and polypropylene fiber is 2.1g:2.1g:100mL:50mL:80g:150g.
[0038] (2) Preparation of epoxy asphalt concrete
[0039] In the preparation process of the low-temperature crack-resistant epoxy asphalt concrete in this embodiment, it is made of the following raw materials, in parts by weight: 45 parts of matrix asphalt, 300 parts of fine aggregate, 520 parts of coarse aggregate, 100 parts of mineral powder, 6 parts of epoxy resin, 4.5 parts of curing agent, 1.5 parts of composite fiber, and 5 parts of rubber powder.
[0040] The preparation process of epoxy asphalt concrete in this embodiment is as follows:
[0041] Mix the base asphalt and rubber powder and preheat to 165°C until the asphalt is completely melted. Maintain the temperature at around 150°C. Mix the epoxy resin and curing agent and add them to the mixing pot. Preheat the coarse aggregate, fine aggregate, and mineral powder to 160°C and add them to the preheated base asphalt. Keep the stirring rate at around 60 rpm. When the temperature reaches around 160°C, add the modified composite fiber and mix. Discharging the material will yield low-temperature-resistant and crack-resistant epoxy asphalt concrete for the anti-seepage panels around pumping and storage reservoirs.
[0042] Example 2
[0043] (1) Preparation of modified composite fibers
[0044] Step 1: Evenly mix epoxycyclohexyl methacrylate (EMCA), 2-methyltetrahydrofuran (2-MeTHF), and 1,8-diazabicycloundec-7-ene (DBU). Simultaneously, introduce nitrogen to protect the reagents. Raise the temperature to 50-60°C and, using a magnetic stirrer at 100 rpm, add the silane coupling agent KH560. Stir thoroughly for 3.5 hours to obtain an intermediate for later use. The ratio of EMCA, 2-MeTHF, and DBU used is 0.2 mol: 0.6 mol: 0.1 mol: 55 mL.
[0045] Step 2: Mix the intermediate, 1-mercaptoethyl-3-methylimidazolium bromide, and anhydrous acetone, purge with nitrogen, maintain the temperature at 60°C, use a magnetic stirrer at 75 rpm, and stir thoroughly for 30 minutes. Then, slowly add boron trifluoride etherate dropwise, raise the temperature to 60°C, react for 2 hours, and then remove the acetone by low-temperature distillation to obtain a modified silane coupling agent. The ratio of the intermediate, 1-mercaptoethyl-3-methylimidazolium bromide, anhydrous acetone, and boron trifluoride etherate is 0.1 mol: 0.1 mol: 125 mL: 0.075 mol.
[0046] Step 3: Dry the basalt fiber at a constant temperature of 200°C, remove it, and allow it to cool naturally. Then, soak it in anhydrous ethanol to remove surface oil and impurities. Rinse it with deionized water and dry it in an oven set at 70°C. Soak the basalt fiber in a 5% thioglycolic acid solution for 1 hour. Remove it, rinse it with deionized water, and dry it in an oven set at 70°C to obtain a basalt fiber intermediate. The ratio of thioglycolic acid solution to basalt fiber is 800ml:80g.
[0047] Step 4: Dibenzoyl peroxide powder is placed in an acetone solution to prepare a 20% dibenzoyl peroxide solution. The solution is then placed in a heatable magnetic stirring device and the temperature is controlled at 70°C to fully dissolve the dibenzoyl peroxide. Polypropylene fiber is placed in the prepared dibenzoyl peroxide solution and placed in a thermostat at 65°C for full soaking for 1 hour. The soaked polypropylene fiber is removed and placed in a ventilated area to dry naturally. It is then rinsed with deionized water and fully dried in an oven set at 75°C to obtain a polypropylene fiber intermediate. The ratio of dibenzoyl peroxide solution to polypropylene fiber is 1L:200g.
[0048] Step 5: Mix the modified silane coupling agent and ethanol solution, adjust the pH to 4 with dilute hydrochloric acid, maintain the temperature at 50°C, and thoroughly mix for 1 hour. Then, add the basalt fiber intermediate and the polypropylene fiber intermediate, stir thoroughly, remove, and dry to obtain a modified fiber intermediate. The ratio of the modified silane coupling agent, basalt fiber intermediate, and polypropylene fiber intermediate is 60g:80g:200g.
[0049] Step 6: Take graphene oxide and molybdenum disulfide powder, use 3% sodium polyacrylate (PAAS) solution to disperse the powder, and simultaneously use ultrasonic treatment power of 500W. During the ultrasonic treatment process, use a microsyringe to dropwise add 5% FeCl3 solution, and treat for 45 minutes to obtain a mixed solution. The modified fiber intermediate is completely immersed in the mixed solution, and simultaneously uses water bath ultrasonic treatment with power of 100W for 10 minutes. After drying, a modified composite fiber is obtained. The ratio of graphene oxide, molybdenum disulfide powder, sodium polyacrylate solution, FeCl3 solution, basalt fiber intermediate, and polypropylene fiber is 2.1g:4.2g:100mL:50mL:80g:200g.
[0050] (2) Preparation of epoxy asphalt concrete
[0051] In the preparation process of low-temperature cracking epoxy asphalt concrete in this embodiment, the following raw materials are used, in parts by weight: 48 parts of matrix asphalt, 330 parts of fine aggregate, 580 parts of coarse aggregate, 130 parts of mineral powder, 8 parts of epoxy resin, 5.5 parts of curing agent, 2 parts of composite fiber, and 5.5 parts of rubber powder.
[0052] The preparation process of epoxy asphalt concrete in this embodiment is as follows:
[0053] Mix the base asphalt and modified rubber powder and preheat to 175°C until the asphalt is completely melted. Maintain the temperature at around 150°C. Mix the epoxy resin and curing agent and add them to a mixing pot. Coarse aggregate, fine aggregate, and mineral powder are preheated to 160°C and added to the preheated base asphalt. Stir at a rate of around 80 rpm. When the temperature reaches around 150°C, add the modified composite fiber and graphene and mix. This yields low-temperature-resistant and crack-resistant epoxy asphalt concrete for anti-seepage panels around pumping reservoirs.
[0054] Example 3
[0055] (1) Preparation of modified composite fibers
[0056] Step 1: Evenly mix epoxycyclohexyl methacrylate (EMCA), 2-methyltetrahydrofuran (2-MeTHF), and 1,8-diazabicycloundec-7-ene (DBU). Nitrogen is introduced to protect the reagents. The temperature is raised to 60°C. A magnetic stirrer is used at 100 rpm. A silane coupling agent, KH560, is added and stirred for 3-4 hours to obtain an intermediate for later use. The ratio of EMCA, 2-MeTHF, and DBU is 0.2 mol: 0.6 mol: 0.1 mol: 55 mL. EMCA and DBU catalyze the epoxy ring-opening reaction, enhancing stability.
[0057] Step 2: Mix the intermediate, 1-mercaptoethyl-3-methylimidazolium bromide, and anhydrous acetone, purge with nitrogen, maintain the temperature at 65°C, use a magnetic stirrer at 90 rpm, and stir thoroughly for 30 minutes. Then, slowly add boron trifluoride etherate dropwise, raise the temperature to 60°C, react for 2 hours, and then remove the acetone by low-temperature distillation to obtain a modified silane coupling agent. The ratio of the intermediate, 1-mercaptoethyl-3-methylimidazolium bromide, anhydrous acetone, and boron trifluoride etherate is 0.1 mol: 0.12 mol: 100 mL: 0.1 mol.
[0058] Step 3: Dry the basalt fiber at a constant temperature of 200°C, remove it, and allow it to cool naturally. Then, soak it in anhydrous ethanol to remove surface oil and impurities. Rinse it with deionized water and dry it in an oven set at 70°C. Soak the basalt fiber in a 5% thioglycolic acid solution for 1 hour. Remove it, rinse it with deionized water, and dry it in an oven set at 70°C to obtain a basalt fiber intermediate. The ratio of thioglycolic acid solution to basalt fiber is 800ml:120g.
[0059] Step 4: Add benzoyl peroxide powder to an acetone solution to prepare a 20% benzoyl peroxide solution. The solution is then placed in a heatable magnetic stirring device and the temperature is controlled at 70°C to fully dissolve the benzoyl peroxide. Polypropylene fiber is placed in the prepared benzoyl peroxide solution and placed in a thermostat at 65°C for 1 hour. The soaked polypropylene fiber is removed and placed in a ventilated area to dry naturally. The fiber is then rinsed with deionized water and dried in an oven set at 75°C to obtain a polypropylene fiber intermediate. The ratio of benzoyl peroxide solution to polypropylene fiber is 1 L:150 g.
[0060] Step 5: Mix the modified silane coupling agent and ethanol solution, adjust the pH to 5 with dilute hydrochloric acid, maintain the temperature at 55°C, and thoroughly mix for 1.5 hours. Then, add the basalt fiber intermediate and the polypropylene fiber intermediate, stir thoroughly, remove, and dry to obtain a modified fiber intermediate. The ratio of the modified silane coupling agent, basalt fiber intermediate, and polypropylene fiber intermediate is 60g:120g:150g.
[0061] Step 6: Disperse graphene oxide and molybdenum disulfide powders with a 3% sodium polyacrylate (PAAS) solution. Ultrasonicate at 500W. During the ultrasonication process, add a 5% FeCl₃ solution dropwise using a microsyringe for 1 hour to obtain a mixed solution. Completely immerse the modified fiber intermediate in the mixed solution and ultrasonicate in a water bath at 150W for 0.5 hours. After drying, a modified composite fiber is obtained. The ratio of graphene oxide, molybdenum disulfide powder, sodium polyacrylate solution, FeCl₃ solution, basalt fiber intermediate, and polypropylene fiber is 4.2g:2.1g:100mL:50mL:120g:150g.
[0062] (2) Preparation of epoxy asphalt concrete
[0063] In the preparation process of low-temperature crack-resistant epoxy asphalt concrete in this embodiment, the following raw materials are used, in parts by weight: 52 parts of matrix asphalt, 300 parts of fine aggregate, 600 parts of coarse aggregate, 140 parts of mineral powder, 9 parts of epoxy resin, 6 parts of curing agent, 2 parts of composite fiber, and 5 parts of rubber powder.
[0064] The preparation process of epoxy asphalt concrete in this embodiment is as follows:
[0065] Mix the base asphalt and modified rubber powder and preheat to 160°C until the asphalt is completely melted. Maintain the temperature at around 150°C. Mix the epoxy resin and curing agent and add them to a mixing pot. Coarse aggregate, fine aggregate, and mineral powder are preheated to 160°C and then added to the preheated base asphalt. Stir at a rate of around 70 rpm. When the temperature reaches around 160°C, add the modified composite fiber and graphene and mix. This mixture is the low-temperature-resistant and crack-resistant epoxy asphalt concrete for the anti-seepage panels around pumping reservoirs.
[0066] Example 4
[0067] (1) Preparation of modified composite fibers
[0068] Step 1: Evenly mix epoxycyclohexyl methacrylate (EMCA), 2-methyltetrahydrofuran (2-MeTHF), and 1,8-diazabicycloundec-7-ene (DBU). Nitrogen is introduced to protect the reagents. The temperature is raised to 60°C. A magnetic stirrer is set at 100 rpm. Silane coupling agent KH560 is added and stirred for 4 hours to obtain an intermediate for later use. The ratio of EMCA, 2-MeTHF, and DBU used is 0.2 mol: 0.6 mol: 0.1 mol: 55 mL.
[0069] Step 2: Mix the intermediate, 1-mercaptoethyl-3-methylimidazolium bromide, and anhydrous acetone, purge with nitrogen, maintain the temperature at 65°C, use a magnetic stirrer at 90 rpm, and stir thoroughly for 0.5 h. Then, slowly add boron trifluoride etherate dropwise, raise the temperature to 60°C, react for 2 hours, and then remove the acetone by low-temperature distillation to obtain a modified silane coupling agent. The ratio of the intermediate, 1-mercaptoethyl-3-methylimidazolium bromide, anhydrous acetone, and boron trifluoride etherate is 0.1 mol: 0.12 mol: 125 mL: 0.1 mol, introducing a thiol group to react with the epoxy group.
[0070] Step 3: Dry the basalt fiber at a constant temperature of 200°C, remove it, and allow it to cool naturally. Then, soak it in anhydrous ethanol to remove surface oil and impurities. Rinse it with deionized water and dry it in an oven set at 70°C. Soak the basalt fiber in a 5% thioglycolic acid solution for 1 hour. Remove it, rinse it with deionized water, and dry it in an oven set at 70°C to obtain a basalt fiber intermediate. The ratio of thioglycolic acid solution to basalt fiber is 800ml:120g.
[0071] Step 4: Dibenzoyl peroxide powder is placed in an acetone solution to prepare a 20% dibenzoyl peroxide solution. The solution is then placed in a heatable magnetic stirring device and the temperature is controlled at 70°C to fully dissolve the dibenzoyl peroxide. Polypropylene fiber is placed in the prepared dibenzoyl peroxide solution and placed in a thermostat at 65°C for full soaking for 1 hour. The soaked polypropylene fiber is removed and placed in a ventilated area to dry naturally. It is then rinsed with deionized water and dried in an oven set at 75°C to obtain a polypropylene fiber intermediate. The ratio of dibenzoyl peroxide solution to polypropylene fiber is 1L:300g.
[0072] Step 5: Mix the modified silane coupling agent and ethanol solution, adjust the pH to 5 with dilute hydrochloric acid, maintain the temperature at 55°C, and thoroughly mix for 1.5 hours. Then, add the basalt fiber intermediate and the polypropylene fiber intermediate, stir thoroughly, remove, and dry to obtain the modified fiber intermediate. The ratio of the modified silane coupling agent, basalt fiber intermediate, and polypropylene fiber intermediate is 60g:120g:300g.
[0073] Step 6: Disperse graphene oxide and molybdenum disulfide powders with a 3% sodium polyacrylate (PAAS) solution. Ultrasonicate at 500W. During the ultrasonication process, add a 5% FeCl₃ solution dropwise using a microsyringe for 1 hour to obtain a mixed solution. Completely immerse the modified fiber intermediate in the mixed solution and ultrasonicate in a water bath at 150W for 0.5 hours. Dry the mixture to obtain a modified composite fiber. The ratio of graphene oxide, molybdenum disulfide powder, sodium polyacrylate solution, FeCl₃ solution, basalt fiber intermediate, and polypropylene fiber is 2.1g:8.4g:100mL:50mL:120g:300g.
[0074] (2) Preparation of epoxy asphalt concrete
[0075] In the preparation process of low-temperature crack-resistant epoxy asphalt concrete in this embodiment, it is made of the following raw materials, calculated by weight: 55 parts of matrix asphalt, 350 parts of fine aggregate, 650 parts of coarse aggregate, 150 parts of mineral powder, 10 parts of epoxy resin, 6.5 parts of curing agent, 3 parts of composite fiber, and 7 parts of rubber powder.
[0076] The preparation process of epoxy asphalt concrete in this embodiment is as follows:
[0077] Mix the base asphalt and modified rubber powder and preheat to 170°C until the asphalt is completely melted. Maintain the temperature at around 150°C. Mix the epoxy resin and curing agent and add them to a mixing pot. Coarse aggregate, fine aggregate, and mineral powder are preheated to 160°C and added to the preheated base asphalt. Stir at a rate of around 90 rpm. When the temperature reaches around 150°C, add the modified composite fiber and graphene and mix. This yields low-temperature-resistant and crack-resistant epoxy asphalt concrete for anti-seepage panels around pumping reservoirs.
[0078] Comparative Example 1
[0079] The low-temperature resistant and crack-resistant epoxy asphalt concrete for the anti-seepage panel around the pumped storage reservoir given in this comparative example is different from that in Example 4 only in that no modification treatment is performed on the basalt fiber and the polypropylene fiber.
[0080] Comparative Example 2
[0081] The low-temperature resistant and crack-resistant epoxy asphalt concrete for the anti-seepage panel around the pumping storage reservoir given in this comparative example is different from that in Example 4 only in that the silane coupling agent KH560 is not treated with epoxycyclohexyl methacrylate (EMCA), 2-methyltetrahydrofuran (2-MeTHF), and 1,8-diazabicycloundec-7-ene (DBU).
[0082] Comparative Example 3
[0083] The low-temperature resistant and crack-resistant epoxy asphalt concrete for the anti-seepage panel around the pumped storage reservoir given in this comparative example is different from that in Example 4 only in that graphene oxide and molybdenum disulfide powder are not used.
[0084] Comparative Example 4
[0085] The low-temperature resistant and crack-resistant epoxy asphalt concrete for the anti-seepage panel around the pumped storage reservoir given in this comparative example is different from that in Example 4 only in that no rubber powder is used.
[0086] Performance testing:
[0087] In order to verify the low-temperature splitting resistance and flexural strength of the low-temperature resistant and crack-resistant epoxy asphalt concrete for the anti-seepage panel around the pumped storage reservoir of the present invention, according to the "Test Procedure for Hydraulic Asphalt Concrete" (DL / T5362-2018), the extreme engineering environment was simulated, and control groups at -10°C and -20°C were set. The epoxy asphalt concrete was made into standard specimens. The splitting and flexural performance results of the asphalt concrete are shown in Table 1.
[0088] Table 1 Splitting and bending properties of asphalt concrete
[0089]
[0090] According to the test results in Table 1, it can be found that the epoxy asphalt concrete after adding composite fibers has significantly improved its low-temperature splitting strength and low-temperature flexural tensile strength. The splitting strength and flexural tensile strength are both greater than the relevant requirements in the "Specifications for Construction of Hydraulic Asphalt Concrete" (SL514-2013) and "Test Procedures for Hydraulic Asphalt Concrete" (DL / T5362-2018). By adding modified composite fibers and rubber powder, the asphalt concrete's resistance to low temperatures and cracking is significantly improved. This asphalt concrete is expected to become an ideal hydraulic material for anti-seepage panels around pumped storage reservoirs.
[0091] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, various equivalent transformations can be made to the technical solutions of the present invention, and these equivalent transformations all fall within the scope of protection of the present invention.
Claims
1. Low temperature resistant and crack resistant epoxy asphalt concrete for anti-seepage panels around pumped storage reservoirs, characterized by: The low-temperature resistant and crack-resistant epoxy asphalt concrete includes, by weight, 300-350 parts of fine aggregate, 520-650 parts of coarse aggregate, 100-150 parts of mineral powder, 45-55 parts of matrix asphalt, 5-7 parts of rubber powder, 6-10 parts of epoxy resin, 4.5-6.5 parts of curing agent, and 1.5-3 parts of modified composite fiber.
2. The method for preparing low-temperature resistant and crack-resistant epoxy asphalt concrete according to claim 1, characterized in that: The steps include: Preheat the base asphalt and rubber powder until they are completely melted and keep them warm; Add epoxy resin and curing agent, mix and stir; Preheat the coarse aggregate, fine aggregate and mineral powder and add them into the matrix asphalt, mix and stir; The modified composite fiber is added, mixed and stirred to obtain low-temperature resistant and crack-resistant epoxy asphalt concrete.
3. A method for preparing a modified composite fiber, characterized in that: The steps include: Step 1, preparing an intermediate: epoxycyclohexyl methacrylate, 2-methyltetrahydrofuran, and 1,8-diazabicycloundec-7-ene are mixed, nitrogen is introduced, the temperature is set to 50-60° C., a silane coupling agent KH560 is added, and the reaction is stirred to obtain an intermediate; Step 2, preparing a modified silane coupling agent: taking the intermediate, 1-mercaptoethyl-3-methylimidazolium bromide, and anhydrous acetone, mixing them, passing nitrogen protection, setting the temperature to 60°C-65°C, slowly adding boron trifluoride ether solution dropwise after stirring, and removing acetone by low-temperature distillation after the reaction to obtain a modified silane coupling agent; Step 3, preparing a basalt fiber intermediate: soaking the basalt fiber in anhydrous ethanol, rinsing with deionized water, and then drying; soaking the basalt fiber in a thioglycolic acid solution, rinsing, and then drying to obtain a basalt fiber intermediate; Step 4, preparing a polypropylene fiber intermediate: soaking the polypropylene fiber in a dibenzoyl peroxide solution, then taking it out, rinsing it, and drying it to obtain a polypropylene fiber intermediate; Step 5, preparing a modified fiber intermediate: mixing the modified silane coupling agent and the ethanol solution, adjusting the pH value to 4-5, and setting the temperature to 45-55° C.; Adding basalt fiber intermediate and polypropylene fiber intermediate, stirring, taking out and drying to obtain a modified fiber intermediate; Step 6, preparing a modified composite fiber: dissolving graphene oxide and molybdenum disulfide powder in a sodium polyacrylate solution, ultrasonically treating the solution, and simultaneously adding FeCl3 solution dropwise to obtain a mixed solution; adding the modified fiber intermediate to the mixed solution, ultrasonically treating the solution, taking it out and drying it to obtain a modified composite fiber.
4. The method for preparing the modified composite fiber according to claim 3, wherein: In step 1, the ratio of epoxycyclohexyl methacrylate, 2-methyltetrahydrofuran, 1,8-diazabicycloundec-7-ene, and KH560 silane coupling agent is 0.2 mol: 0.5 mol-0.6 mol: 0.05 mol-0.1 mol: 45-55 ml.
5. The method for preparing the modified composite fiber according to claim 3, wherein: In step 2, the ratio of the intermediate, 1-mercaptoethyl-3-methylimidazolium bromide, anhydrous acetone, and boron trifluoride ether solution is 0.1 mol: 0.1-0.12 mol: 100-125 mL: 0.05-0.1 mol.
6. The method for preparing the modified composite fiber according to claim 3, wherein: In step 3, the ratio of the amount of thioglycolic acid solution to the amount of basalt fiber is 800 ml: 80 g-120 g.
7. The method for preparing the modified composite fiber according to claim 3, wherein: In step 4, the ratio of the amount of dibenzoyl peroxide solution to the amount of polypropylene fiber is 1L:150g-300g.
8. The method for preparing the modified composite fiber according to claim 3, wherein: In step 5, the ratio of the amount of the modified silane coupling agent, the basalt fiber intermediate, and the polypropylene fiber intermediate is 60g:80g-120g:150g-300g.
9. The method for preparing the modified composite fiber according to claim 3, wherein: In step 6, the ratio of graphene oxide, molybdenum disulfide powder, sodium polyacrylate solution, FeCl3 solution, basalt fiber intermediate, and polypropylene fiber is 2.1g-4.2g:2.1g-8.4g:100mL:50mL:80g-120g:150g-300g.
10. The method for preparing the modified composite fiber according to claim 3, wherein: In step 6, the concentration of sodium polyacrylate is 3% and the concentration of FeCl3 solution is 5%.
Citation Information
Patent Citations
Fiber-reinforced asphalt mixture and preparation method thereof
CN108117306A
Ultrathin overlay composite modified asphalt concrete and preparation method thereof
CN116119979A
Rubber powder epoxy asphalt cementing material for expansion joints, prefabricated structure, preparation method and application of rubber powder epoxy asphalt cementing material
CN116396014A
Multi functional asphalt composition for road pavement with fine dust absorption, waterproof, snow removing and insulation effect and the deteriorated asphalt road pavement reparing method thereof
KR102252921B1
Curing agent for epoxy resins, and epoxy resin composition obtained using same
US20180327629A1